Syphilis masquerading as focal segmental glomerulosclerosis. (June 2014) - Hartley, AJ; Rajakariar, R; Sheaff, M; Buckland, M; Goh, B; O'Connell, R
A patient referred to the genitourinary clinic for positive syphilis serology was found to have symptoms and signs of nephrotic syndrome. A renal biopsy showed focal segmental glomerulosclerosis (FSGS). Doxycycline 200 mg twice daily for 28 days coincided with considerable decrease in proteinuria and rise in serum albumin, suggesting a causal relationship.